Efektywność wykorzystania czynników produkcji w produkcji mleka w Polsce i w wybranych krajach na świecie - Kołoszycz, Ewa (Efficiency of Production Factors Use in Milk Production in Poland and in Selected Countries in the World, 2005)
Productivity of main production factors: land, capital and labor in milk production are the main case of the article. 16 farms from different regions of the world have been analysed. The main reasons of differences in productivity level among farms are shown in the article. In general productivity in CEEC and Asian countries is much lower than in other countries (except capital and land productivity in some cases).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 456-461